Factors contributing to the low number of blood donors among employed residents in Oshatumba village, Namibia - Daniel O. Ashipala; Medusalem H. Joel (AOSIS, 2023)
Background: Blood transfusion plays a significant role in maternal and child-care interventions, as well as by saving lives following natural disasters. Ignorance and fear among the general population in Namibia limit the numbers of blood donors, leaving the Namibian Blood Transfusion Services (NAMBTS) with insufficient donations for hospital patients. A review of the literature did not disclose publications on the factors that contribute to the low number of blood donors in Namibia, despite the urgent need for an increased pool of blood donors. Aim: The aim was to explore and describe the factors contributing to the low number of blood donors among the employed residents of the Oshatumba village, Oshana Region, Namibia. Settings: Interviews were conducted at a peri-urban village located in the eastern part of the Oshakati District in the Oshana Region. Methods: A qualitative methodology utilising explorative, descriptive and contextual strategies. Data were collected by means of individual, in-depth, semi-structured interviews with 15 participants, who were selected through convenience sampling. Results: The study discovered three themes: (1) the concept of blood donation; (2) factors contributing to low blood donations and (3) practical suggestions to increase the low uptake of blood donations. Conclusion: The findings of this study revealed that individual health status, religious beliefs and misconceptions associated with blood donations are among the factors that cause a low level of blood donations. Contribution: The research findings can be used to develop strategies and targeted interventions to increase the number of blood donors.